Patient blood management for cardiovascular surgery: Clinical practice consensus statement - Amatya, Ashish Govinda; Sharma, Apurb; Shrestha, Battu Kumar; Nepal, Bipin; Paneru, Hem Raj; Shrestha, Amit; Baral, Ravi; Gurung, Arjun; Panthee, Nirmal; Gandhi, Ajay; Goerlinger, Klaus; Aryal, Diptesh; et al. (Nepalese Heart Journal, 2023)
Anemia, blood loss and transfusion related issues following cardiovascular surgery are detrimental to patient outcomes. This document provides a concise overview of the Patient Blood Management for Cardiovascular Surgical Practice in Nepal. The consensus aims to optimize patient outcomes and enhance the quality of care in cardiovascular surgery by emphasizing evidence-based approaches to blood management. The document covers a range of topics, including preoperative assessment, intraoperative strategies, and postoperative care, with a focus on minimizing unnecessary blood transfusions, promoting hemostasis, and reducing the risk of complications. By adhering to this consensus, healthcare professionals can contribute to improved patient safety and overall clinical effectiveness in the field of cardiovascular surgery.